Angiomotin isoform 2 promotes binding of PALS1 to KIF13B at primary cilia and regulates ciliary length and signaling - Morthorst, Stine Kjær (2023)
The kinesin-3 motor KIF13B functions in endocytosis, vesicle transport and regulation of ciliary length and signaling. Direct binding of the membrane-associated guanylate kinase (MAGUK) DLG1 to the MAGUK-binding stalk domain of KIF13B relieves motor autoinhibition and promotes microtubule plus-end-directed cargo transport. Here, we characterize angiomotin (AMOT) isoform 2 (p80, referred to as Ap80) as a novel KIF13B interactor that promotes binding of another MAGUK, the polarity protein and Crumbs complex component PALS1, to KIF13B. Live-cell imaging analysis indicated that Ap80 is concentrated at and recruits PALS1 to the base of the primary cilium, but is not a cargo of KIF13B itself. Consistent with a ciliary function for Ap80, its depletion led to elongated primary cilia and reduced agonist-induced ciliary accumulation of SMO, a key component of the Hedgehog signaling pathway, whereas Ap80 overexpression caused ciliary shortening. Our results suggest that Ap80 activates KIF13B cargo binding at the base of the primary cilium to regulate ciliary length, composition and signaling.